Implementation Supplementary Feeding Program and Infant and Young Child Feeding Counseling as a Stunting Prevention Program During Pandemic - Febriyati, Tasya Sabila; Diah Herawati, Dewi Marhaeni; Megawati, Gina (Jurnal Kesehatan Prima, 2022)
Large-Scale Social Restrictions (PSBB) as an effort to reduce the transmission of COVID-19 pandemic and COVID-19 pandemic itselfÂ hasan impact on stunting prevention program carried out byÂ PublicÂ Health Centers (Puskesmas), including the Supplementary Feeding Program (PMT) and Infant and Young Child Feeding Counseling (PMBA) and this condition occurs in various regions in Indonesia, including Bandung. This study aimedÂ to examine the implementation of PMT and PMBA counseling program during the COVID-19 pandemic in the workingÂ area of the BuahbatuÂ PublicÂ Health Center as one of the public health centers with the highest stunting number in Bandung. This study using the mixed methods concurrent embedded method, in this study quantitative data were used to determine percentage of PMT and PMBA counseling coverage before the COVID-19 pandemic (2017-2019) and during the COVID-19 pandemic (in 2020) as supporting qualitative data done withÂ in-depth interviews.Â The results showed that the stunting rate increased every year especially during the COVID-19 pandemic, PMT and PMBA counseling continued to be carried out during the COVID-19 Pandemic even though at the beginning of the COVID-19 pandemic the program was hampered, so several adjustments and innovation were made by the public health center officers and cadres to made percentage of stunting children in 2020 is 23,20%, percentage of PMT coverage in 2020 is 100% but percentage for PMBA counseling coverage in 2020 is only 9%.Â PMT runs smoothly so that all children get PMT, while PMBA counseling runs but is only given to a few stunted children because of some obstacles.